MINUTES ON APPLICATION AND AMENDMENTS OF FORESTS REGULATION (1857) - Stanković, Uroš (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The article sheds light on several data about application of Forests Regulation (1857) and its amendments. Forests Regulation was aimed to procure better protection of Serbian woods, prescribing restrictive conditions under which deforestation was allowed and the obligation to dismantle illegal enclosures. None of the two aims was turned into reality. In an attempt to broaden their lands, people were persistant in prohibited wood-cutting. Deforestation culminated in 1859, for the reason that due to a dynastic change new government was still unable to acquire authority. Plus, the Government was unsure about people not resisting to destruction of enclosures and was thus compelled to tacitly legalize illegaly occupied lands. Formally at the initiative of state bodies, but practically at the insistence of people, the Regulation was amended three times. Firstly, the procedure according to which a piece of land is attributed to the poor was significantly simplified. Tax for wood-cutting permits was reduced to a great extent. Alterations regarding enclosure dismantling largely relativized the Regulation’s provions in terms of that matter. The Regulation was doomed to failure due to three major factors. People had no consciousness about importance of forests and considered them self-regenerative. However, the authorities tasked with protection of woods were not any better either. On many occasions, they silently approved wood-cutting. Moreover, village and county-chiefs were not rarely actively engaged as accomplices in that crime.